EXCITON-PHONON INTERACTION IN ALKALI HALIDE CRYSTALS BY LOW TEMPERATURE UNIAXIAL STRESS - Myasnikova, L.; Sagimbaeva, Sh.; Shunkeyev, K. (Recent Contributions to Physics, 2018)
For the first time on the basis of luminescence spectroscopy the influence of low temperature elastic uniaxial stress on the process of exciton-phonon interaction in crystal KI was studied by registering temperature quenching of self-trapped exciton’s (STE) luminescence. An increase of activation energy of STE luminescence quenching is detected, which is interpreted by the increase of potential barrier of non-irradiative channel of STE decay on radiation defects in crystal KI.  The experimental data were used for the calculation of the exciton active fluctuation’s frequency and Huang-Rhys factor in crystal KI. The crystals KI  lattice symmetry lowering at low temperature uniaxial stress leads to the frequency increase of exciton active fluctuations. This is an evidence for exciton-phonon interaction weakening, which leads to probability increase of exciton irradiative annihilation proved by experimental data.